2022
DOI: 10.3390/v14061341
|View full text |Cite
|
Sign up to set email alerts
|

The Potyviral Protein 6K1 Reduces Plant Proteases Activity during Turnip mosaic virus Infection

Abstract: Potyviral genomes encode just 11 major proteins and multifunctionality is associated with most of these proteins at different stages of the virus infection cycle. Some potyviral proteins modulate phytohormones and protein degradation pathways and have either pro- or anti-viral/insect vector functions. Our previous work demonstrated that the potyviral protein 6K1 has an antagonistic effect on vectors when expressed transiently in host plants, suggesting plant defenses are regulated. However, to our knowledge th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 75 publications
1
19
0
Order By: Relevance
“…According to their function description, these proteins were divided into six categories, namely defense-related, transport-related, metabolism-related, DNA binding, unknown, and membrane-related proteins ( Figure 3 ). In this categorization, defense-related proteins accounted for the most (28%), followed by transport-related proteins (20%), suggesting the involvement of 6K1 in viral movement, which is consistent with previous reports [ 29 , 42 ]. This suggestion was further supported by GO analysis, which revealed that candidate genes were significantly enriched in the transport process and transmembrane transporter activity ( Figure 4 A).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…According to their function description, these proteins were divided into six categories, namely defense-related, transport-related, metabolism-related, DNA binding, unknown, and membrane-related proteins ( Figure 3 ). In this categorization, defense-related proteins accounted for the most (28%), followed by transport-related proteins (20%), suggesting the involvement of 6K1 in viral movement, which is consistent with previous reports [ 29 , 42 ]. This suggestion was further supported by GO analysis, which revealed that candidate genes were significantly enriched in the transport process and transmembrane transporter activity ( Figure 4 A).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the potential interactions found in the Y2H system may not happen during natural infection. However, we have observed the interactions between 6K1 and the Papain family cysteine protease (GmPFCP)/Cysteine protease inhibitors (GmCYSB) that were reported previously [ 42 ], suggesting that the Y2H system is a good system to analyze interaction in vitro. The identification of host factors interacting with 6K1 contributes to the understanding of the molecular mechanism of 6K1 in virus infection.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, the phytohormones have a significant role in controlling plant–potyvirus and plant–insect interactions. For instance, plants can utilize ethylene (ET), jasmonic acid (JA), and salicylic acid (SA) to fight against a variety of phloem-feeding insects, such as aphids, which are the primary insect carrier for potyviruses [ 54 , 64 , 65 , 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…The green peach aphid, Myzus persicae (Sulzer), is a major threat to potatoes due to its ability to adapt to a wide range of plant species [ 27 ] and easily develop an anti-insecticide biotype to maintain homeostasis [ 28 ]. In addition to being a significant plant pest, green peach aphids also serve as a vector for potyviruses, resulting in significant production losses [ 29 , 30 ]. When Myzus persicae feeds on the plant epidermis, it transmits potato virus Y, cucumber mosaic virus [ 31 ], and PVY in a non-persistent mode, making management a major concern [ 32 ].…”
Section: Introductionmentioning
confidence: 99%